2015
DOI: 10.1128/aem.00580-15
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level and Species-Specific Associations between Phytoplankton and Particle-Associated Vibrio Species in Delaware's Inland Bays

Abstract: Vibrio species are an abundant and diverse group of bacteria that form associations with phytoplankton. Correlations between Vibrio and phytoplankton abundance have been noted, suggesting that growth is enhanced during algal blooms or that association with phytoplankton provides a refuge from predation. Here, we investigated relationships between particle-associated Vibrio spp. and phytoplankton in Delaware's inland bays (DIB). The relative abundances of particle-associated Vibrio spp. and algal classes that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 73 publications
4
32
0
1
Order By: Relevance
“…The sharp increase in Vibrio abundance observed in recent years (e.g., 2000 onward) is concomitant with an increase of certain phytoplankton species, notably diatoms (e.g., Thalassiosira spp., Rhizosolenia imbricata), and a decline in abundance of other species, especially dinoflagellates (e.g., mainly Ceratium species). These results agree with recent work that demonstrated a significant correlation between Vibrio abundance in seawater and phytoplankton, with higher correlations with diatoms compared with dinoflagellates (48). One possible explanation for this finding is that diatoms genera, such as Thalassiosira, use chitin as a structural component of the silica cell wall, and it has been recently shown that some Vibrio species interact with diatom-derived chitin to foster their environmental persistence (42).…”
Section: Long-term Variation In Vibrio Abundance Relative To Multidecsupporting
confidence: 92%
“…The sharp increase in Vibrio abundance observed in recent years (e.g., 2000 onward) is concomitant with an increase of certain phytoplankton species, notably diatoms (e.g., Thalassiosira spp., Rhizosolenia imbricata), and a decline in abundance of other species, especially dinoflagellates (e.g., mainly Ceratium species). These results agree with recent work that demonstrated a significant correlation between Vibrio abundance in seawater and phytoplankton, with higher correlations with diatoms compared with dinoflagellates (48). One possible explanation for this finding is that diatoms genera, such as Thalassiosira, use chitin as a structural component of the silica cell wall, and it has been recently shown that some Vibrio species interact with diatom-derived chitin to foster their environmental persistence (42).…”
Section: Long-term Variation In Vibrio Abundance Relative To Multidecsupporting
confidence: 92%
“…Quantitative and qualitative differences in phytoplankton species composition may lead to pronounced differences in bacterioplankton species composition (Pinhassi et al 2004). In particular, the relationship between vibrios and specific groups of phytoplankton is controversial, and some authors suggest a preferential association with dinoflagellates (Eiler et al 2006), while others suggest a minor link between the two groups (Main et al 2015). Our data show a positive relation between the abundances of vibrios and of the dinoflagellate Ostreopsis at Llavaneres.…”
Section: Is Abundance Of Vibrios Linked To Ostreopsis Concentration?supporting
confidence: 55%
“…Vibrios have been detected on a large variety of biological surfaces, especially animals (Thompson et al 2004, Baffone et al 2006, Main et al 2015, and are also associated with various types of organic particles of non-animal origin (Lyons et al 2007, Froelich et al 2013. Recently, there has been evidence that vibrios can remain free-living (Mourino-Perez et al 2003, Worden et al 2006, Eiler et al 2006, although little is known on the factors determining whether they remain free-living versus particle-attached (Takemura et al 2014).…”
Section: Are Vibrios Found Preferentially Attached To Particles?mentioning
confidence: 99%
“…Vibrios, including those belonging to the Harveyi clade, are known to be able to associate with (micro)algae (Nealson and Hastings, 2006;Manset et al, 2013;Main et al, 2015), which (like terrestrial plants) are known to produce various indole analogues as auxin hormones (Stirk et al, 2013;Lu and Xu, 2015). Auxins have been reported to affect various phenotypes in terrestrial bacteria (Spaepen and Vanderleyden, 2011).…”
Section: Discussionmentioning
confidence: 99%